PENGARUH PENGETAHUAN, KEMAMPUAN, DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. MASTER CASH & CREDIT RANTAUPRAPAT - Dewi Puji Astuti; Siti Lam’ah Nasution; Yudi Prayoga (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the effect of knowledge of work discipline and communication skills on employee performance at PT. Master Cash & Credit Rantauprapat. Data collection in this study was conducted through survey approaches, interviews and documentation. This study had a sample of 40 respondents where the entire population was sampled. The data analysis tool used in this study used SPSS (Statistical Product Software Solution). The data analysis technique in this research is descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (t test), simultaneous significant test (F test), and determination coefficient test (R2). That the F test result is 87. 386 with a significant level of 0.000, while the Ftable value of 3.332. When compared to the value of fcount 87.386> ftable 3.332 at α 5%, the conclusion is that simultaneously the Knowledge, Work Discipline and Communication Ability variables have a positive and significant effect on Employee Performance, that the tcount value for the Knowledge variable is 0.321, Ability is -0.057, Work Discipline is equal to 3.605, and communication of 4.391 with a significant value of each independent variable (4.163), (0.000). Whereas for the t-table value in the t distribution statistical table with level of test α = 5% and Dk = n - k, 40 -5 = 35 with a sig value of 5%, the value of t table = 1.869. Based on the criteria that if the value of tcount> ttable H0 is rejected , on the other hand tcount <ttable, H0 is accepted.  : (0.321> 1.869), (-0.057 <1.869), (3.605> 1.869), (4.391> 1.869).